Are linear elastic material properties relevant predictors of the cyclic fatigue resistance of dental resin composites? - Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2014)
The aim of this study was to measure the linear elastic material properties of direct dental resin composites and correlate them with their fatigue strength under cyclic loading.Bar specimens of twelve resin composites were produced according to ISO 4049 and tested for elastic modulus (Emod) in 3-point bending (n=10), flexural strength (FS) (n=15) and single-edge-notch-beam fracture toughness (FT) (n=15), both in 4-point bending. Using the same specimen geometry, the flexural fatigue strength (FFS) was determined using the staircase approach after 10(4) cycles at 0.5 Hz in 4-point bending (n=25). The observation of the fracture surface and fracture profiles was conducted using a scanning electron microscope in order to evaluate the respective fracture mechanisms according to the two different loading conditions.Materials were ranked differently according to the tested parameters. Only weak correlations were found between any of the initial properties and FFS or strength loss. The best correlation to FFS was found to be the Emod (r(2)=0.679), although only slightly. Crack path in both loading conditions was mainly interparticle, with the crack propagating mainly within the matrix phase for fatigued specimens and eventually through the filler/matrix interface for statically loaded specimens. Fracture of large particles or prepolymerized fillers was only observed in specimens of FS and FT. Initial properties were better associated with microstructural features, whereas the fatigue resistance showed to be more dependent on aspects relating to the matrix phase.Our results show that linear elastic properties such as elastic modulus, flexural strength and fracture toughness are not good descriptors of the fatigue resistance of dental resin composite under cyclic bending, and may therefore have limited clinical relevance.
EVALuna2:24662